Governance challenges in China’s urban health care system – the role of stakeholders - Bork, Tabea; Kraas, Frauke; Yuan, Yuan (ERDKUNDE, 2011)
The article at hand aims at contributing to a deeper understanding of problems in China’s urban health system governance by comparing levels of influence and the roles of different stakeholder groups – government bodies, public, private and illegal health care providers, patients and their social networks, paying institutions, social organizations, and the civil society – in the production and reproduction of the layout of the health care system in the city of Guangzhou. Primary data was collected in several fieldwork studies in Guangzhou City between December 2006 and January 2009 and includes 27 in-depth interviews with administrative officials, health care providers and NGO representatives as well as 70 in-depth interviews and a quantitative survey with 450 rural-urban migrants. We use the actor-centred institutionalism approach by Mayntz and Scharpf (1995) and Scharpf (2000) which we combine with Archer’s (1995) morphogenetic approach in order to develop an analysis tool. The findings show that although hierarchical steering by the municipal administrative units in Guangzhou is officially still in place, new corporate agents have emerged, such as influential hospital managers, social organizations and NGOs that, together with the multiple adaption and circumvention strategies of primary agents, patients and health care providers, are significantly reshaping the health system. Considering China’s current debate on the general type of health system that should be put in place we argue that it is necessary to restructure the functions and influences of stakeholders in the health system if any such reforms should be successful in improving public health. The basis for this should be the establishment of an all-embracing health governance framework, which should include independent third-party supervision and monitoring and which requires overall reforms of the general state governance structures as well as a more profound integration of interests and collaboration of all stakeholders.